Investigating Dimensions of Teacher Reflective Practice at Language Teachers - Purnama, M. Rokhman; Hanifah, Hanifah; Abdullah, Mohamad Syarief; Sogen, Afrianto T. L.; Santosa, Made Herry; Parwati, Ni Nyoman (Universitas Negeri Makassar, 2025)
This study examines the implementation of teachers ‘reflective practice in elementary schools in Bekasi, Indonesia, by analyzing teachers’ self-reflection strategies, challenges, and their impact on improving teaching. Reflective teaching practices have been increasingly recognized as a fundamental approach to improving teaching effectiveness and promoting professional growth among educators. By utilizing a mixed methods approach, data was collected from 198 language teachers through the Teacher Reflective Practice Questionnaire and in-depth interviews. The study explored five main dimensions of teacher reflection: interpersonal, intrapersonal, critical, behavioral, and strategic reflection. The results highlight the need for structured professional development programmers and institutional support to facilitate sustainable reflective teaching practices. In addition, the study underscores the importance of collaboration among educators, encouraging peer-to-peer discussions and self-assessment methods to enhance reflective practice. The findings show that teachers demonstrated high levels of interpersonal and behavioral reflection, with strong engagement in student interactions and classroom adjustments as there are still challenges in integrating reflective strategies into daily teaching due to time constraints, lack of institutional support, and limited professional development opportunities. In addition, teachers show varying levels of engagement in strategic reflection, especially in adopting technology-based reflection tools. By addressing these gaps, policymakers and educational institutions can design more effective training programmers that support teachers to become lifelong learners. Ultimately, fostering a culture of reflection in teaching not only improves educators’ professional competence, but also enhances students’ learning experiences and outcomes